Study the formation of callus and single cell of Kiwi (Actinidia deliciosa) - Nhut, Duong Tan; Thu Ha, Tran Thi; Huong, Trinh Thi; Cuong, Hoang Van; Huy, Nguyen Phuc (Academia Journal of Biology, 2013)
This study was conducted to study the callus induction and the effect of plant growth regulators, pH of medium, sugar concentration and medium volume on single cell culture of Kiwi in vitro. Results showed that in vitro Kiwi leaf explant size of 1×1 cm gave the best callus induction on MS medium with 0.8 mg/l 2,4-D. Leaf explant placed with the abaxial surface down on the medium induced more callus formation than that placed with the adaxial surface down on the medium (0,99 g fresh weight and 0.067 g dry weight with the abaxial surface down; 0.82 g fresh weight and 0.055 g dry weight with the adaxial surface down). Number of single cells were the highest (342 cells/µl) in 250 ml culture vessel with 20 ml liquid MS medium with 0.6 mg/l 2,4-D, 60 g/l sucrose and pH at 6.1. In addition, the most appropriate intervals of callus subculture in shaking liquid culture is 16 days. This research is a prerequisite for further studies of single cell of Kiwi.